Perancangan Sistem Informasi Layanan Cabut Kost Berbasis Progressive Web Apps - Siswantono, Muhammad Gibran; Nurrahman, Ahmad Arif (UNISBA Press, 2023)
Abstract. In the current business landscape, digital transformation has become essential for companies to survive and thrive. One such company is Cabut Kost, a newly established moving company in Indonesia. Initially catering to students, Cabut Kost provides a convenient solution for their moving needs, eliminating the hassle of packing and shipping. However, to enhance efficiency and expand their market reach, the company aims to transition from a conventional to a digital business model.The primary focus of this paper is to develop a prototype mobile application for Cabut Kost and implement new digital business processes. To achieve this, a Problem Solving Framework will be employed to identify and analyze the company's existing business flows. The research will progress through various stages, including inputting the company's information system, designing business processes, and creating an information system design using the waterfall method.By adopting this digital approach, Cabut Kost aims to facilitate faster communication with customers, ultimately leading to increased customer satisfaction. The analysis and design of the application and website will utilize the System Development Life Cycle (SDLC) approach. Key components, such as the Use Case Diagram, flow map, Entity Relationship Diagram (ERD), and prototype design supported by Glide Apps, will be incorporated to ensure a comprehensive digital solution.The main objective of the Cabut Kost application is to streamline the process of moving goods, providing users with easy access to order services, manage pick-up and delivery schedules, and monitor shipment statuses. It is crucial for Cabut Kost to adapt to new technologies continuously, enabling them to stay competitive and meet customer expectations. Implementing the proposed business applications and analysis will significantly improve service quality and simplify the digital ordering process for Cabut Kost's customers. Abstrak. Cabut Kost adalah perusahaan pindahan baru di Indonesia yang membantu mahasiswa berpindah dari kos lama ke kos baru atau kembali ke kampung halaman. Untuk bertahan dan meningkatkan efisiensi, mereka ingin bertransformasi secara digital dengan menciptakan aplikasi seluler dan menerapkan proses bisnis digital. Penelitian akan menggunakan Framework Pemecahan Masalah untuk mengidentifikasi aliran bisnis perusahaan. Tahap berikutnya adalah menginput sistem informasi perusahaan, mendesain proses bisnis, dan sistem informasi. Analisis data akan dilakukan dengan metode waterfall, meliputi analisis kebutuhan, desain, pengembangan, dan pengujian sistem. Dengan aplikasi dan situs web, komunikasi dengan pelanggan akan lebih cepat dan meningkatkan kepuasan mereka.Analisis dan desain akan menggunakan metode siklus hidup pengembangan sistem, termasuk Use Case Diagram (UCD), peta aliran, Entity Relationship Diagram, dan prototipe aplikasi dengan Glide Apps. Sistem informasi Cabut Kost bertujuan untuk membantu proses pengiriman barang lebih efisien. Pelanggan dapat dengan mudah memesan layanan transfer barang, mengatur jadwal pengambilan dan pengiriman, serta memantau status pengiriman. Cabut Kost perlu beradaptasi dengan teknologi baru agar tetap kompetitif dan meningkatkan kepuasan pelanggan. Melalui aplikasi dan analisis yang dijelaskan dalam UCD, peta aliran, dan ERD, kualitas layanan akan ditingkatkan, dan proses pemesanan digital menjadi lebih sederhana bagi pelanggan.